2002
DOI: 10.1063/1.1500781
|View full text |Cite
|
Sign up to set email alerts
|

Capacitance and conductance characterization of ferrocene-containing self-assembled monolayers on silicon surfaces for memory applications

Abstract: Self-assembled monolayers of 4-ferrocenylbenzyl alcohol attached to silicon provided the basis for electrolyte-molecule-silicon capacitors. Characterization by conventional capacitance and conductance techniques showed very high capacitance and conductance peaks near ∼0.6 V associated with charging and discharging of electrons into and from discrete levels in the monolayer owing to the presence of the redox-active ferrocenes. The reversible charge trapping of these molecules suggest their potential application… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
104
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(105 citation statements)
references
References 10 publications
0
104
0
1
Order By: Relevance
“…277 As discussed in Section 3, provided that care is taken, silicon-carbon linked organic monolayers offer a convenient approach to chemically and electrically well-passivated silicon surfaces. The organic-semiconductor structure promises to expand the performances and applications of conventional semiconductor devices, with novel biosensing interfaces 259 and high-density memory storage 40,44,215 among the envisioned devices. For example, surface-bound molecules either charged or polarized can influence the energy levels near the surface (i.e.…”
Section: Summary and Perspectivesmentioning
confidence: 99%
“…277 As discussed in Section 3, provided that care is taken, silicon-carbon linked organic monolayers offer a convenient approach to chemically and electrically well-passivated silicon surfaces. The organic-semiconductor structure promises to expand the performances and applications of conventional semiconductor devices, with novel biosensing interfaces 259 and high-density memory storage 40,44,215 among the envisioned devices. For example, surface-bound molecules either charged or polarized can influence the energy levels near the surface (i.e.…”
Section: Summary and Perspectivesmentioning
confidence: 99%
“…By designing and positioning the proper molecules in the device the desired functionality is obtained. SAMs have been used as molecular memories [21], molecular wires [22], and have exhibited negative differential resistance [23].…”
Section: A Self-assembled Monolayers (Sams) On Solid Substratesmentioning
confidence: 99%
“…By attaching reduction-oxidation (redox) molecules as a floating gate in the complementary metal-oxide-semiconductor (CMOS) structure, one also creates a high-impedance nonamperometric electrode for probing the molecular redox states, in contrast to the low-impedance connections used in cyclic voltammetry (CyV) [6]- [9]. Previous studies have shown capacitance and conductance peaks associated with the charging and the discharging of the carriers stored at the MOs [7] and CyV hysteresis owing to the redox of molecules attached to the SiO 2 surface [6], [8], [9].…”
mentioning
confidence: 99%